Effects of twelve pesticides on larvae of oysters (Crassostrea gigas) and on two species of unicellular marine algae (Isochrysis galbana and Chaetoceros calcitrans) - His, Edouard; Seaman, Matthias (Acte du Conseil International pour l'Exploration de la Mer, C.M. 1993/E:22, 1993)
The effects of seven herbicides, four insecticides and one molluscicide were tested at concentrations of up to 10 mg/l on larvae of oysters, Crassostrea gigas (9 days exposure), and on laboratory cultures of the algae Isochrysis galbana and Chaeloceros calcilrans (21 days exposure). Ali of the pesticides tested had significant toxic effects on at least one of the test organisms. The strongest effects were those of lindane and isoproturon on survival and growth of C.gigas larvae, and of isoproturon and carbetamide on growth of Isochrysis and Chaeloceros cultures. The log-probit model for the relationship between dosage and effect, and Haber's rule for the relationship between duration of exposure and effect, hardly ever applied to our data. In sorne cases we found marked toxicity threshholds, and in others there were pronounced hormesis effects. We characterize five types of responses to prolonged toxicant exposure, including delayed toxic effects (sometimes following initial hormesis) , and initial growth inhibition with subsequent recovery (sometimes ending in hormesis). The great variability of response (depending on duration of exposure, toxicant concentration and test species), is a reminder that the effects of pollutants on the marine environment cannot be assessed by simple methods (e.g. short-term bioassays with one or two test species). This contrasts with the requirement for easy routine methods of pollution assessment for monitoring and management purposes.